1991
DOI: 10.1093/bja/66.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Incremental Spinal Anaesthesia Using a 32-Gauge Catheter With Extradural Anaesthesia for Elective Caesarean Section

Abstract: Forty-three mothers who had requested regional anaesthesia for elective Caesarean section were allocated randomly to receive either extradural anaesthesia with pH-adjusted 2% lignocaine with 1/200,000 adrenaline, or incremental spinal anaesthesia using a 32-gauge catheter with 0.5% plain bupivacaine. Increments of lignocaine or bupivacaine were given with the aim of achieving a block from T4 to S5. The spinal catheter was quicker to place (median 3 min, range 1-45 min, compared with median 10 min, range 1.5-50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(11 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…In this study, two of the 22 women in the CSA group were excluded, one because of failure to identify the subarachnoid space and the other because the catheter could not be placed. 24 This represents a failure rate of 9% compared with 20% in our study. Again there are significant differences between this study and ours as a 32-guage catheter through needle was used.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…In this study, two of the 22 women in the CSA group were excluded, one because of failure to identify the subarachnoid space and the other because the catheter could not be placed. 24 This represents a failure rate of 9% compared with 20% in our study. Again there are significant differences between this study and ours as a 32-guage catheter through needle was used.…”
Section: Discussionmentioning
confidence: 44%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] There are few studies in the literature assessing the efficacy and safety of CSA in obstetrics, whether descriptive or comparative studies. [22][23][24][25][26] The primary objective of this study was to assess the efficacy and safety of CSA with the catheter-overneedle technique (Spinocath Ò ) when used for elective cesarean delivery.…”
Section: Introductionmentioning
confidence: 99%
“…For spinal needles, the duration of PDPH ranged from one to seven days. 15,22,32,34,[37][38][39]44 Further analysis of the data on onset and duration was not attempted as the data were confounded by differences in prophylactic and therapeutic interventions between studies and by uncertainty on the length of patient follow-up. Median patient follow-up was six days in the eight studies 9,17,27,31,33,37,39,49 that reported length of follow-up along with data on onset or duration of PDPH.…”
Section: Dp and Pdph Ratesmentioning
confidence: 99%
“…Continuous spinal anaesthesia is reported to offer more haemodynamic stability over continuous epidural or single-dose spinal anaesthesia [21][22][23][24]. Continuous spinal anaesthesia is reported to offer more haemodynamic stability over continuous epidural or single-dose spinal anaesthesia [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%